Characterization of the Water Masses in the Shelf Region of the Bering and Chukchi Seas With Fluorescent Organic Matter. Issue 11 (11th November 2019) - Yamashita, Youhei; Yagi, Yuki; Ueno, Hiromichi; Ooki, Atsushi; Hirawake, Toru
Abstract: Pacific water is an important nutrient source for sustaining biological production in the Chukchi Sea, western Arctic Ocean, which is one of the productive regions in the world. Therefore, to understand the impacts of future environmental changes on biological production in the sea, it is crucial to understand the origins, modification processes, and spatiotemporal variations of the water masses from the Bering Sea with changes in nutrient concentrations. To improve water mass analysis in the shelf regions of the Bering and Chukchi Seas, we observed levels of humic‐like fluorescent organic matter (FOMH ) by using an in situ fluorometer directly connected to a temperature‐salinity sensor during a cruise in the early summer of 2013 and evaluated the potential of FOMH as a third parameter of water mass analysis. The levels of FOMH were different among specific water masses in the region, and FOMH seemed to behave semiconservatively in the shelf regions of the Bering and Chukchi Seas during the early summer of 2013. The distributional pattern of FOMH implies that FOMH estimated by the in situ fluorometer has the potential to (1) separate warm water into riverine‐affected Alaskan Coastal Water and historically photobleached summer Bering Basin Water; (2) distinguish the Anadyr Water, which has low FOMH levels and high nutrient concentrations, from the Bering Shelf Water; and (3) determine different formation/modification processes of dense shelf water that contains high nutrient concentrations. Plain Language Summary: The continental shelves of the northern Bering Sea and the Chukchi Sea are known to be the area characterized by a high abundance of organisms from phytoplankton to marine mammals and seabirds. Such a high density of marine organisms is sustained by intensive primary production induced by inputs of enough nutrients. The inputs of nutrients to the region are possibly sensitive to climate change. To project future changes in nutrient supply to the region, the present mechanism of nutrient supply should be quantitatively understood. To date, however, the mechanism is poorly determined because the origin and modification of water masses that convey nutrients have not been well understood. This study measured humic‐like fluorescent organic matter, products during the decay and transformation of biogenic remains, in addition to temperature and salinity by in situ sensors to characterize the water masses in the shelf region of the Bering and Chukchi Seas during the early summer of 2013. The levels were clearly different among water masses defined by temperature and salinity and characterized by different concentrations of nutrients, indicating that humic‐like fluorescent organic matter is useful to refine the water masses in the region for quantitative understanding of the mechanism of nutrient supply. Key Points: Distributions of fluorescent organic matter in the Bering and Chukchi Seas are measured by an in situ fluorometer to refine water masses Fluorescent organic matter is useful for identifying Alaskan Coastal Water, summer Bering Basin Water, and nutrient‐rich Anadyr Water Formation/modification processes of dense shelf water that is rich in nutrients can be evaluated by fluorescent organic matter